Development of a decision support tool for use of 3D terrestrial laser scanning for piping designs - Morgan, Joseph; Mostafiz, Rubayet Bin; Friedland, Carol (Frontiers in Built Environment, 2025)
The design and renovation of industrial plant piping systems demand high levels of dimensional accuracy to prevent costly errors and delays. Traditional methods for field data collection are often time-consuming and susceptible to human error, which can compromise the quality and efficiency of piping designs. This study explores the development of a decision support tool (DST) for the use of three-dimensional (3D) terrestrial laser scanning (TLS) in piping designs, aiming to enhance precision and efficiency in the engineering process. Despite the advantages of TLS technology, there is no dedicated decision support tool to help piping designers determine the appropriateness of using TLS for piping designs. This research employs a triangulation methodology, including a literature review, semi-structured interviews, and case study, to identify key factors influencing the adoption of TLS and to validate the proposed DST. The findings demonstrate that TLS offers significant accuracy, time savings, and safety advantages, making it a valuable tool for industrial piping design projects.